Phase II trial of imatinib mesylate in recurrent, biomarker positive, ovarian cancer (Southwest Oncology Group Protocol S0211). Issue 4 (1st July 2007) - Alberts, D. S.; Liu, P. Y.; Wilczynski, S. P.; Jang, A.; Moon, J.; Ward, J. H.; Beck, J. T.; Clouser, M.; Markman, M.
Abstract : Platinum-resistant ovarian cancer continues to be a difficult therapeutic problem. Clearly, molecularly targeted agents should be evaluated in this patient population. Patients were eligible for this phase II study with stage III or IV ovarian cancer, whose tumor expressed Kit (CD117) or platelet-derived growth factor receptor (PDGFR) and with relapse of measurable disease within 6 months of completing frontline, platinum- and taxane-based chemotherapy. Patients were treated daily with 400 mg of imatinib mesylate orally. It was assumed that the agent would be of no further interest if the population response rate was less than 10%. A two-stage design was used for patient accrual. A total of 34 patients were registered to the study. Of these, 15 were found to be ineligible or not evaluable (8 because their tumor samples were negative for both DC117 and PDGFR). Of 19 evaluable patients, 2 (11%) tested positively for c-Kit and 17 (89%) tested positively for PDGFR. There were no objective responders. Thirteen patients (68%) had increasing disease or symptomatic deterioration, and six (32%) went off protocol during the first month due to adverse events. Median progression-free survival was 2 months (95% CI 1–3 months) and median overall survival was 10 months (95% CI 6–18 months). Eleven percent of patients experienced grade 4 hematologic/metabolic toxicity and 37% experienced grade 3 nonhematologic toxicity. We conclude that imatinib mesylate as a single agent does not appear to have useful clinical activity in c-Kit and/or PDGFR positive, recurrent ovarian cancer in heavily pretreated patients with ovarian cancer